FLOUTS OF THE COOPERATIVE PRINCIPLE MAXIMS IN SBY'S PRESIDENTIAL INTERVIEWS - ZAMAN, Fahrus (2010)
This thesis analyzed presidential interviews of the President of Republic of Indonesia, Susilo Bambang Yudoyono (SBY), based on Grice's theory of the Cooperative Principles (CP). This study employed a qualitative research design and the data were three transcripts of interview discourse between SBY and eight Indonesian journalists which were obtained through the presidential official website: http://www.presidentsby.info. The research questions include the ways of SBY in flouting the CP maxims in his presidential interviews and the functions of the flouts are. The research revealed that SBY flouted all the CP maxims (Quantity, Quality, Relation and Manner) and the maxim of Quantity was frequently flouted (8 times of 18). Meanwhile, there were four ways used by SBY in flouting the CP maxims, i.e. hedging, indirectness, open answer and detailed element. The function of the flouts, i.e. face saving acts (FSA), self-protection, awareness, politeness, interestingness, control of information, elaboration and ignorance. The function of face saving acts was frequently employed by SBY to maintain the face of his government. This research also revealed that CP maxims are not universal. The phenomena of flouts in SBY's presidential interviews did not reduce the cooperativeness especially the flouts of the maxim of Quantity. For journalists, over-information and lengthy explanation given by the interviewee may help them to achieve a rich background and in-depth understanding of a phenomenon. Mutual understanding among the participants also keeps the cooperativeness of conversation. It means that the CP depends not only on the amount of information, accuracy, way and relevance but also on the aspects of tolerance and cultural background of participants of the conversation.